Outcome analysis of decompressive craniectomy in a tertiary center in Nepal - Rajbhandari, Binod; Aryal, Sameer; Karki, Anjan Singh; Bhattachan, Maya; Sedain, Gopal (Grande Medical Journal, 2021)
Introduction: Decompressive Craniectomy (DC) is used as a surgical procedure to treat intractable intracranial hypertension when all other treatments have failed. Role of DC for various pathologies still is uncertain. Our study’s aim was to describe the demographic, clinical, and operative characteristics of patients who underwent DC for various conditions at our tertiary care center and to identify subpopulations that benefit the most from surgical intervention.Materials and Methods: All patients who underwent DC in Department of Neurosurgery, Green City Hospital, Kathmandu, Nepal from January 1, 2018 to December 31, 2020 were included in this study. This was a retrospective study and different variables affecting the outcome were analyzed. The follow up period was six months.Results: During the course of our study, 68 patients underwent DC with age 21-77 years with a mean age of 46.0 ±13.3 years. The gender ratio was 1.6:1. (42 males to 26 females). Glasgow Outcome Scale (GOS) was used to assess patient outcome. There was better outcome of DC in age 8 had unfavorable outcomes in 32.2% of cases (p=0.0018). Favorable outcomes were more common in DC performed for trauma, aneurysm, and sinus thrombosis than ischemic stroke and hemorrhagic stroke. Favorable outcome was seen with intact bilateral pupillary reflexes (59%; p=0.022) in our study.Conclusions: The outcome of decompressive craniectomy was better in patients with trauma, cerebral venous thrombosis and aneurysmal subarachnoid hemorrhage than in patients with intracerebral hemorrhage and ischemia. The preoperative pupillary status (bilateral equal and reactive), GCS > 8 and age less than 50 were the variables associated with a favorable outcome in these patients.